A standardised mobile internet (wireless) environment for mobilising healthcare. (11th May 2004) - Wickramasinghe, Nilmini; Sharma, Sushil K.; Goldberg, Steve
Healthcare has become one of the foremost domestic issues in the USA; healthcare costs represent about 14% of the Gross Domestic Product. Business and industry view the increased costs of healthcare and healthcare benefits as impediments to their ability to compete in international markets. Various health organisations and researchers are trying to get relevant research findings and successful innovations and management practices from other industries, countries, and healthcare organisations. This chapter discusses the findings from INET's study on mobile internet (wireless) technology initiatives in healthcare by Ontario Hospitals in Canada. This research has shown that mobile/wireless solutions for healthcare can achieve four critical goals to: 1) improve patient care; 2) reduce transaction costs; 3) increase healthcare quality; and 4) enhance teaching and research. Integral to the incorporation of wireless initiatives is the reliance on the healthcare portal and the underlying three-tier web based architecture. The same or similar initiatives can be exploited by other hospitals to incorporate a wireless/m-commerce solution to enable hospitals to operate effectively and efficiently in today's competitive and costly healthcare environment.